The Physical Self in Motion: Within-Person Change and Associations of Change in Self-Esteem, Physical Self-Concept, and Physical Activity in Adolescent Girls - AŞÇI, FEVZİYE HÜLYA (HUMAN KINETICS PUBL INC, 2014)
The purpose of this study was to examine patterns of within-person change, and associations of change, in global self-esteem (GSE), physical self-perceptions (PSP), and physical activity in a sample of 705 Canadian adolescent girls over three measurements points and 24 months. The Physical Self-Perceptions Profile (PSPP) was used to measure GSE and PSP, and the Physical Activity Questionnaire for Adolescents (PAQ-A) was used to assess physical activity. Latent growth curve models were used to analyze the data. All PSP variables except for body attractiveness demonstrated significant average decline, but also significant was the change in between-person heterogeneity. Change in GSE and PSP was moderately to strongly related on a between-person level and weakly to moderately associated on a within-person level. Change in physical activity was related to change in the majority of the PSP variables but not to change in GSE.
Keywords: change; latent growth curve; physical self-perceptions; physical activity; self-esteem; COVARIANCE STRUCTURE-ANALYSIS; PERCEPTIONS; EXERCISE; ANXIETY; GENDER; DOMAIN